Implementation of Metasploit Framework on Android Platform in a Single Network - Muhammad Fitra Gemilang; Arif Senja Fitrani; Mochamad Alfan Rosid; S Sumarno (CV. Media Digital Publikasi Indonesia, 2026)
This study discusses the implementation of the Metasploit Framework on the Android platform within a single network. The objective of this research is to analyze the vulnerability of Android devices to backdoor attacks using penetration testing tools. The payload in the form of an APK file was created using msfvenom and tested on Android devices within a local network. The results showed successful exploitation, including access to SMS, call logs, and device location. This study highlights the need for security awareness among Android users and the importance of preventive measures.